2021
DOI: 10.1021/acs.jafc.1c05451
|View full text |Cite
|
Sign up to set email alerts
|

5-n-Alkylresorcinol Profiles in Different Cultivars of Einkorn, Emmer, Spelt, Common Wheat, and Tritordeum

Abstract: 5-n-Alkylresorcinols (AR) are bioactive compounds found in the edible parts of many cereals. Here, saturated and unsaturated homologues, including the oxidized forms 5-(2′-oxo) AR and their plant metabolites, were profiled by ultrahighperformance liquid chromatography−ion mobility separation−high-resolution mass spectrometry in 18 cultivars of einkorn, emmer, spelt, common wheat, and tritordeum, cultivated in two consecutive years under uniform agronomic conditions. The average content of AR ranged between 672… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 51 publications
4
39
0
Order By: Relevance
“…Elder et al [ 66 ] found the optimum antioxidant activity at an intermediate alkyl chain length (C21:0), after which the activity declined. By characterizing the alkylresorcinol homologue profiles in spelt and bread wheat, several studies [ 9 , 10 , 61 ] found that the predominant homologue was C21:0 in both species, which represented almost half of the total alkylresorcinol content, followed by C19:0 and C23:0. By comparison of those three homologues in bread and spelt wheat, Pedrazzani et al [ 9 ] reported higher values for C21:0 and C19:0 in spelt wheat than in bread wheat varieties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Elder et al [ 66 ] found the optimum antioxidant activity at an intermediate alkyl chain length (C21:0), after which the activity declined. By characterizing the alkylresorcinol homologue profiles in spelt and bread wheat, several studies [ 9 , 10 , 61 ] found that the predominant homologue was C21:0 in both species, which represented almost half of the total alkylresorcinol content, followed by C19:0 and C23:0. By comparison of those three homologues in bread and spelt wheat, Pedrazzani et al [ 9 ] reported higher values for C21:0 and C19:0 in spelt wheat than in bread wheat varieties.…”
Section: Discussionmentioning
confidence: 99%
“…By characterizing the alkylresorcinol homologue profiles in spelt and bread wheat, several studies [ 9 , 10 , 61 ] found that the predominant homologue was C21:0 in both species, which represented almost half of the total alkylresorcinol content, followed by C19:0 and C23:0. By comparison of those three homologues in bread and spelt wheat, Pedrazzani et al [ 9 ] reported higher values for C21:0 and C19:0 in spelt wheat than in bread wheat varieties. Additionally, significantly higher value was observed for the ratio of the two dominant homologues (C21:0/C23:0) in spelt compared to bread wheat [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations